The Expression of Osteoclastogenesis-Associated Factors and Osteoblast Response to Osteolytic Prostate Cancer Cells - Morrissey, Colm (2010)
BACKGROUND: Prostate cancer (PCa) has a propensity to metastasize to bone. Tumor cells replace bone marrow and can elicit an osteoblastic, osteolytic, or mixed bone response. Our objective was to elucidate the mechanisms and key factors involved in promoting osteoclastogenesis in PCa bone metastasis. METHODS: We cultured osteoblast-like MC3T3-E1 cells with conditioned medium (CM) from PC-3 and C4-2B cells. MC3T3-E1 mineralization decreased in the presence of PC-3 CM, whereas C4-2B CM had no effect on mineralization. Using oligo arrays and validating by real-time PCR, we observed a decrease in the expression of mineralization-associated genes in MC3T3-E1 cells grown in the presence of PC-3 CM. In addition, PC-3 CM induced the expression of osteoclastogenesis- associated genes IGFBP-5, IL-6, MCP-1, and RANKL while decreasing OPG expression in MC3T3-E1 cells. Furthermore, CM from MC3T3-E1 cells cultured in the presence of PC-3 CM, in association with soluble RANKL, increased osteoclastogenesis in RAW 264.7 cells. Investigation of PCa metastases and xenografts by immunohistochemistry revealed that the osteoclastic factor IL-6 was expressed in the majority of PCa bone metastases and to a lesser extent in PCa soft tissue metastases. In vitro it was determined that soluble IL-6R (sIL-6R) was necessary for IL-6 to inhibit mineralization in MC3T3-E1 cells. RESULTS: PC-3 cells inhibit osteoblast activity and induce osteoblasts to produce osteoclastic factors that promote osteoclastogenesis, and one of these factors, IL-6, is highly expressed in PCa bone metastases. CONCLUSIONS: IL-6 may have an important role in promoting osteoclastogenesis in PCa bone metastasis through its’ interaction with sIL-6R.